Accurate digital interface with low‐component count for sine‐cosine shaft encoders. Issue 25 (1st December 2018) - Nandapurkar, K.B.; Anoop, C.S.; Dutta, P.K.
Abstract : A digital high‐accuracy interface for sine–cosine shaft encoders (SCE) is proffered. The outputs of SCE vary as a sine and cosine functions of shaft angle. The proposed interface processes these outputs and renders a linear direct‐digital output for 360° operating range. The interface has minimal dependence on many circuit non‐idealities including the phase error of quadrature oscillator. The performance of the interface is verified using simulation and emulation‐based studies. Furthermore, the interface is tested with a magneto‐resistance‐based SCE. Test results show that the output non‐linearity remains around 0.27% for typical values of phase errors. The interface also possesses features such as low‐component count, high linearity, direct‐digital output etc.